PERTUMBUHAN DAN KELULUSAN HIDUP TERIPANG PASIR (Holothuria scabra) YANG DIPELIHARA DI KERAMBA JARING APUNG - Padang, Anita; Sangadji, Madehusen; Lukman, Eryka; Subiyanto, Rochman (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2017)
Production of sand sea cucumbers is only relying on direct collection from the nature to meet market demand. This study aims to determine the rate of growth and the survival rate of sand sea cucumbers reared in floating net cages to the treatment of chicken manure and waste giving sago as an enrichment habitat in order to stimulate the growth of benthic diatoms as sand sea cucumbers food. Sea cucumbers are maintained as much as 90 individual with treatments of sago waste, chicken manure and a mixture of sago waste and chicken manure. In the maintenance container was given sedimentary sand and seagrass leaves of Enhalus accoroides. Measurement of weight growth is conducted every two weeks, and at a time measuring water quality parameters of temperature, salinity, pH, DO, phosphate, nitrate and ammonium. The results showed the negative growth rate, namely of -0.439% with sago waste; -0.529% chicken manure; and -0.383% mixture of sago waste and chicken manure. Meanwhile, the survival rate with sago waste was 73.33%; with chicken manure 80%; and with the mixture of sago waste and chicken manure 86.67%. It means that water quality for cultivating sand sea cucumber was optimum, except for nitrate. ABSTRAK Produksi teripang pasir selama ini hanya mengandalkan hasil tangkapan dari alam, sehingga dalam memenuhi permintaan pasar perlu dilakukan usaha budidaya. Penelitian ini bertujuan mengetahui laju pertumbuhan dan tingkat kelulusan hidup teripang pasir yang dipelihara dalam keramba jaring apung dengan perlakuan pemberian kotoran ayam dan limbah sagu sebagai bahan pengayaan habitat untuk merangsang pertumbuhan diatom bentik sebagai makanan teripang pasir. Teripang pasir yang dipelihara sebanyak 90 ekor dengan tiga perlakuan pakan yaitu : limbah sagu, kotoran ayam serta campuran limbah sagu dan kotoran ayam. Pada wadah pemeliharaan diberikan sedimen pasir dan daun lamun Enhalus acoroides. Pengukuran pertumbuhan berat dilakukan setiap dua minggu sekaligus mengukur parameter kualitas perairan yaitu suhu, salinitas, pH, DO, fosfat, nitrat dan amoniak. Hasil penelitian menunjukkan laju pertumbuhan sebesar -0,439% dengan perlakuan limbah sagu, -0,529% dengan kotoran ayam, dan -0,383% dengan campuran limbah sagu dan kotoran ayam. Sementara tingkat kelulusan hidup berturut-turut sebesar 73,33% dengan limbah sagu 80%, dengan kotoran ayam, dan 86,67% dengan campuran limbah sagu dan kotoran ayam. Seluruh parameter kualitas perairan adalah optimal untuk budidaya teripang pasir, kecuali nitrat. Kata Kunci: Teripang pasir, Kotoran ayam, Limbah sagu, Keramba jaring apung